2021
DOI: 10.11591/ijict.v10i2.pp93-103
|View full text |Cite
|
Sign up to set email alerts
|

Data mining techniques for lung and breast cancer diagnosis: A review

Abstract: <p>Today, cancer counted as the riskier disease than the other diseases in the globe. There are many cancer forms like leukemia, skin cancer, and stomach cancer but lung and breast cancer are the most common forms that many people suffered from. Cancer is the disease that cell has grown rapidly and abnormally that is why treating it is somehow tough in some cases but it can be controlled if it is detected in the initial stage. Data-mining classification algorithms had a vital role in predicting and recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In that 206 are normal images and 113 are breast cancer images [22]. The proposed approach is compared with other classifiers like Naive Bayes (NB) [23], k-nearest neighbor (KNN) [24], decision tree (DT) [23], support vector machine (SVM) [24] and random forest (RF) [25].…”
Section: Resultsmentioning
confidence: 99%
“…In that 206 are normal images and 113 are breast cancer images [22]. The proposed approach is compared with other classifiers like Naive Bayes (NB) [23], k-nearest neighbor (KNN) [24], decision tree (DT) [23], support vector machine (SVM) [24] and random forest (RF) [25].…”
Section: Resultsmentioning
confidence: 99%
“…A hybrid algorithm was developed in [24] for increasing the security in e-business systems. Data-mining classification algorithms were introduced in [25] to detect the lung and breast cancer diagnose. New approach was developed in [26] to decision-making based on the characterization of cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%
“…University institutions play a decisive role within society, since they seek to educate people who manage to acquire skills, which will be used in their professional development, it is therefore very important to link the role of the university with knowledge management supported by artificial intelligence [13]- [15]. In this context of handling a large amount of data or what we know as data mining, an aspect to be highlighted is the generation of grouping or classification models of objects or entities based on the same characteristic or behavior, which will then be used for the decision making [16]- [18]. In [19]- [23] it is indicated that among the different algorithms used to perform predictive classification models we have the models generated through the vector support machine (VSM) algorithm.…”
Section: Introductionmentioning
confidence: 99%